2004
DOI: 10.1007/bf02975845
|View full text |Cite
|
Sign up to set email alerts
|

Stylopine fromChelidonium majus inhibits LPS-Induced inflammatory mediators in RAW 264.7 cells

Abstract: Stylopine is a major component of the leaf of Chelidonium majus L. (Papaveraceae), which has been used for the removal of warts, papillomas and condylomas, as well as the treatment of liver disease, in oriental countries. Stylopine per se had no cytotoxic effect in unstimulated RAW 264.7 cells, but concentration-dependently reduced nitric oxide (NO), prostaglandin E2 (PGE2), tumor necrosis factor-alpha (TNF-alpha) and interleukin-1beta (IL-1beta), and the IL-6 production and cyclooxygenase-2 (COX-2) activity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Moreover, new antiinflammatory drugs are being discovered and developed based on their effects on signal transduction and as anti-cytokine agents [30]. Previous studies have revealed that LPS-induced inflammatory mediator production by macrophages can be attenuated by isoquinoline alkaloids like berberine, and stylopine [31,32]. Lycorine is one of the most common isoquinoline alkaloids and has a variety of pharmacological activities [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, new antiinflammatory drugs are being discovered and developed based on their effects on signal transduction and as anti-cytokine agents [30]. Previous studies have revealed that LPS-induced inflammatory mediator production by macrophages can be attenuated by isoquinoline alkaloids like berberine, and stylopine [31,32]. Lycorine is one of the most common isoquinoline alkaloids and has a variety of pharmacological activities [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide has been reported to up‐regulate the expression of inflammatory mediators such as IL‐1β, tumour necrosis factor‐α (TNFα), IL‐6, nerve growth factor (NGF), inducible nitric oxide synthase (iNOS) and cyclooxygenase 2 (COX2)/prostaglandin E 2 (PGE 2 ) in RAW264.7 macrophages 11–13 . The nuclear factor‐κB (NF‐κB) signalling pathway is involved in LPS‐induced production of inflammatory mediators in this cell line 12,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide has been reported to up-regulate the expression of inflammatory mediators such as IL-1b, tumour necrosis factor-a (TNFa), IL-6, nerve growth factor (NGF), inducible nitric oxide synthase (iNOS) and cyclooxygenase 2 (COX2)/prostaglandin E 2 (PGE 2 ) in RAW264.7 macrophages. [11][12][13] The nuclear factor-jB (NF-jB) signalling pathway is involved in LPS-induced production of inflammatory mediators in this cell line. 12,14 As a transcription factor, NF-jB plays a key role in the transcriptional regulation of genes of numerous inflammatory mediators including iNOS, COX2, IL-1b, IL-6 and TNFa.…”
Section: Introductionmentioning
confidence: 99%
“…Both alkaloid families are associated with a broad range of biological activities: Many 1-benzyl-1,2,3,4-tetrahydroisoquinolines act as antispasmodic or hypotensive and some, such as norcoclaurine, coclaurine, and N -methylcoclaurine, possess anti-HIV activity in vitro . (2) Berbines show diverse biological activities such as analgesic, sedative, hypnotic, or anti-inflammatory effects,(3) and the non-natural derivative l -chloroscoulerine is currently investigated as a novel treatment of schizophrenia. (4) In addition, tetrahydroisoquinolines have recently been employed as chiral ligands for metal-catalyzed transfer-hydrogenation.…”
Section: Introductionmentioning
confidence: 99%